(untitled) (Global Journal of Medical Research, 2020)
The aims of this cross-sectional study were i) to evaluate the psychometric properties of the Depression Anxiety and Stress Scale (DASS-21) in adults with different temporal conditions of pain; ii) to compare the Depression, Anxiety and Stress subscale scores in different individuals; iii) to estimate the prevalence of negative affectivity; and iv) to elaborate a predictive model considering aspects related to the development of negative affectivity. A total of 1,150 individuals (mean age: 38.6, SD = 10.8 years; 78.9% women) participated. The fit of the model of DASS-21 to the data was estimated by confirmatory strategy. The Depression, Anxiety and Stress mean scores of participants with different temporal conditions of pain were compared. The association between Depression, Anxiety and Stress and the presence or absence of pain was assessed by the chi-square test and odds ratio (OR). A multiple logistic regression model was developed to estimate the probability of negative affectivity in the sample.